2018
DOI: 10.5194/os-2018-114
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arctic Mediterranean Exchanges: A consistent volume budget and trends in transports from two decades of observations

Abstract: Abstract. The Arctic Mediterranean (AM) is the collective name for the Arctic Ocean, the Nordic Seas, and their adjacent shelf seas. Into this region, water enters through the Bering Strait (Pacific inflow) and through the passages across the Greenland-Scotland Ridge (Atlantic inflow) and then modified within the AM. The modified waters leave the AM in several flow branches, which are grouped into two different categories: (1) overflow of dense water through the deep passages across the Greenland-Scotland Ridg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 73 publications
(122 reference statements)
1
34
0
Order By: Relevance
“…This is readily done by reducing the flow south in the KGR column in Table a small amount from −0.64 to −0.41 Sv such that flow north and south match at 8.84 Sv. This 8.84 Sv is larger than the R18 estimate due to the way flow is estimated in the FSC and the inclusion of the FIC (Østerhus et al, ). Given the 18.4 Sv for the southern section we infer that 9.57 Sv (18.4–8.84 Sv) is lost from the upper limb of the MOC between the two key sections.…”
Section: Volume Heat and Freshwater Budgetsmentioning
confidence: 68%
See 2 more Smart Citations
“…This is readily done by reducing the flow south in the KGR column in Table a small amount from −0.64 to −0.41 Sv such that flow north and south match at 8.84 Sv. This 8.84 Sv is larger than the R18 estimate due to the way flow is estimated in the FSC and the inclusion of the FIC (Østerhus et al, ). Given the 18.4 Sv for the southern section we infer that 9.57 Sv (18.4–8.84 Sv) is lost from the upper limb of the MOC between the two key sections.…”
Section: Volume Heat and Freshwater Budgetsmentioning
confidence: 68%
“…The significantly greater loss rate for the Nordic Seas is another way of noting that the temperature difference between the water flowing north and the water spilling back into the North Atlantic is much greater than for either the Labrador Sea or subpolar gyre. It should also be noted that Østerhus et al (; their Table 2) report no long‐term trends of the observed exchanges across the Greenland‐Scotland Ridge. Figure summarizes the partitioning of the MOC fluxes between the Labrador Sea, the subpolar gyre, and the Nordic Seas.…”
Section: Parsing Out the Overturningmentioning
confidence: 93%
See 1 more Smart Citation
“…The OW transport through FBC is detailed by Hansen et al (2015bHansen et al ( , 2016, while the DS overflow is presented by Jochumsen et al (2017). Recent observations and estimates of the overflow across the IFR suggest a mean overflow of less than 0.4 Sv (1 Sv [ 10 6 m 3 s 21 ) (Hansen et al 2018). Observations of overflow across the Wyville-Thomson Ridge (WTR) are available, with some gaps, for 2003-13 and are on average 0.8 Sv (Sherwin et al 2008a;Sherwin 2010).…”
Section: A Datamentioning
confidence: 99%
“…Arrows are approximately scaled proportion to transport. Gray topography is shallower than 750 m. Adapted from Østerhus et al, .…”
Section: Introductionmentioning
confidence: 99%